The Influence of Online Marketing and Service Quality on Customer Satisfaction at Hotel Xtra Bengkulu - Aditia Kurniawan; Iswidana Utama Putra; Yudi Irawan Abi (Jurnal Pusat Manajemen, 2026)
The digital era has changed the interaction between companies and consumers, especially in the hospitality industry, where online marketing and service quality have become very important in increasing customer satisfaction. In this context, Hotel Xtra Bengkulu seeks to understand how these two aspects influence customer satisfaction. The main problem studied is the extent to which online marketing and service quality influence customer satisfaction. This study aims to analyze the influence of online marketing and service quality on customer satisfaction at Hotel Xtra Bengkulu. Based on the problem formulation, the study focuses on three things: (1) does online marketing influence customer satisfaction, (2) does service quality influence customer satisfaction, and (3) do both simultaneously influence customer satisfaction at Hotel Xtra Bengkulu. The research method used is a quantitative approach by distributing questionnaires to 85 respondents, which were determined using the Slovin formula with a 10% error limit. The research data were collected through a Likert scale questionnaire, then analyzed using multiple linear regression analysis with the help of the IBM SPSS Statistics 25 program. The results of the study showed that online marketing (X1) has a positive and significant influence on customer satisfaction with a regression coefficient value of 0.497 and a significance value of 0.000 <0.05. The service quality variable (X2) also has a positive and significant influence on customer satisfaction with a coefficient of 0.439 and a significance value of 0.000 <0.05. The regression equation obtained is Y = 1.690 + 0.497X₁ + 0.439X₂ + e, which shows that both independent variables contribute together to increasing customer satisfaction at Hotel Xtra Bengkulu. Based on the results of the research and discussion, it is recommended that Hotel Xtra Bengkulu continue to strengthen its digital marketing strategy through various online platforms such as social media, websites, and room booking applications, as well as integrating marketing strategies with improved customer service to enrich the guest experience during their stay.